Implementation of Information and Communication System-Based Public Services in the Context of Increasing Satisfaction of Licensing Service Users at the Surabaya City Investment and One-Stop Integrated Services Office - Novita Theresyana Erawati (Lavish Opulent Education, 2025)
This study aims to evaluate the implementation of public service delivery based on information and communication technology through the Online Single Submission (OSS) system at the Investment and One-Stop Integrated Services Office (DPMPTSP) in Surabaya. Using a descriptive quantitative approach and the SERVQUAL framework, the research involved 120 respondents representing users of licensing services. Data were collected through a structured questionnaire and analyzed using descriptive statistics. The findings indicate that the overall quality of OSS-based services is perceived as very good, with reliability emerging as the strongest dimension, particularly in the absence of illegal levies and unofficial intermediaries. Conversely, the assurance dimension received the lowest score, indicating the need for better alignment between service delivery and user expectations. The study concludes that while digital systems improve transparency and procedural integrity, service effectiveness must also be supported by responsive systems, clear communication, and improved technical support. The results provide practical insights for optimizing digital public services and enhancing citizen satisfaction in the context of e-government.